Pequenas e médias empresas no contexto da gestão da qualidade total - José Carlos Teixeira da Silva; Dorival Ferreira (Production)
Este trabalho analisa a gestão da qualidade em organizações, envolvendo pequenas e médias empresas do setor de manufaturados, utilizando um modelo conceitual que envolve aspectos estratégicos e operacionais da gestão da qualidade. Através de referências bibliográficas e pesquisa de campo encaminha uma análise da gestão da qualidade nessas organizações, concluindo que existem dificuldades nesse campo. Existe indicação da necessidade de desenvolvimento de procedimentos e metodologias especificas para essa categoria de organização. This paper discusses the quality management in organizations with respect the strategic and operational aspects, and analyses the stage of traditional small and medium enterprises-SMEs of the manufacture sector, with support of bibliographical references and exploratory research. It was detected some aspects concerning the quality management for those companies: absence of global strategic planning and no practices in conventional tools of quality at factory level Because any regional and cultural characteristics, those firms still get to survive, at short term. However, we denote the necessary introduction of specifics methodologies in quality management for those enterprises.